2014
DOI: 10.1109/tthz.2013.2294018
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Water Vapor and Cloud Cover—Sites for High-Performance THz Applications

Abstract: Abstract-Absorption of terahertz radiation by atmospheric water vapor is a serious impediment for radio astronomy and for long-distance communications. Transmission in the THz regime is dependent almost exclusively on atmospheric precipitable water vapor (PWV). Though much of the Earth has PWV that is too high for good transmission above 200 GHz, there are a number of dry sites with very low attenuation. We performed a global analysis of PWV with high-resolution measurements from the Moderate Resolution Imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Most of the stations in this table are located at elevations above 2600 masl and below 3000 masl. We validated our results using satellite measurements of the upper bound for mean precipitable water vapor (Suen et al 2014, Suen 2016) for those two regions, which is reported to be ∼ 10 − 15 mm in ∼ 20 km resolution maps. This means that it is not implausible to find a site with an even lower water vapor column in one of the regions of interest identified here.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Most of the stations in this table are located at elevations above 2600 masl and below 3000 masl. We validated our results using satellite measurements of the upper bound for mean precipitable water vapor (Suen et al 2014, Suen 2016) for those two regions, which is reported to be ∼ 10 − 15 mm in ∼ 20 km resolution maps. This means that it is not implausible to find a site with an even lower water vapor column in one of the regions of interest identified here.…”
Section: Discussionsupporting
confidence: 58%
“…We compared our results to the work of Suen et al (2014) and Suen (2016), where they obtained global precipitable water vapor maps for 2012 using data from the MODIS instrument on board the Aqua and Terra satellites. Even though raw MODIS data has a potentially higher spatial resolution, the resolution of the processed maps is not fine enough to pinpoint a site location at a precision higher than ∼ 20 km.…”
Section: Comparison To Other Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate work, we analyzed the annual atmospheric precipitable water vapor (PWV) distribution over the entire surface of the Earth using high-resolution remote sensing satellite data and identified sites with the lowest water vapor [7]. This work identified specific dry locations, in addition to well-known astronomical sites, such as the Tibetan Plateau and high peaks in the Western United States, which have very low PWV values.…”
mentioning
confidence: 99%
“…Water vapour in the extratropical lowermost stratosphere may be additionally influenced by changes in isentropic transport from the subtropics (Dessler et al, 2013). Additionally, absorption by atmospheric water vapour of radiation at terahertz and radio frequencies is a serious impediment for radio astronomy and for long-distance communications (Suen et al, 2014). The vertical distribution of water vapour is relevant for all of the effects mentioned.…”
Section: Introductionmentioning
confidence: 99%